A pilot study on a proposed discusion-based information literacy program in the Quezon City Public Library - Krus na Ligas Branch - Valebia, Joanne A. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
With the obvious inadequacy of the public school system in the Philippines, it is apparent that information illiteracy is becoming a threat to future generations. Inadequate structures, facilities, and manpower for the education sector results in the poor development of the future leaders of this country. It is in this light that the study focused on the untapped potential of library and information professionals to supplement and complement the rising need for instruction that leads to the development of information literate independent learners.